Municipal response to the Great Recession: Evidence from small- to medium-sized cities in Georgia and Florida. Issue 4 (5th November 2018) - Christian, Cary; Bush, Jonathan
Abstract : Purpose: The purpose of this paper is to examine the impact of the Great Recession on small- to medium-sized municipalities within the states of Georgia and Florida using a newly developed set of quantitative indices. Design/methodology/approach: An examination of the methods and strategies utilized by individual cities to maintain public service levels despite distressed revenues is performed. From the data, performance measures are developed and used to evaluate the efficacy of the various strategies used by the cities. Outcomes of Georgia municipalities were compared to similarly sized Florida municipalities to study how underlying differences in tax structures and economies might have affected those outcomes. Findings: Georgia and Florida municipalities relied on very different strategies for surviving the recession and its aftermath. Enterprise activities were critically important in both states with transfers to or from governmental activities rationalized in various ways. While Georgia is generally anti-property tax, more than half the Georgia municipalities relied on property tax increases to survive. Municipalities were unable to count on increased intergovernmental revenues during the recession. Finally, even with a tourist activity advantage, Florida municipalities fared only marginally better during and just after the recession, and fared worse four to six years post-recession. Practical implications: The measures developed in this study provide a new, customizable methodology for the evaluation of financial condition that does not require in-depth comparisons to peers. Social implications: Small- and medium-sized cities, and especially those in rural areas, are worthy of targeted research to better understand their unique problems. Originality/value: This research is novel in utilizing a fiscal condition methodology that can be applied to a single municipality and does not require comparisons to peers for validity. However, it represents a very intuitive and customizable tool for making comparisons between municipalities of any size when such comparisons are desired. Additionally, the focus of this study is on small- to medium-sized municipalities which generally do not receive as much research attention as larger cities.